Association between dental visits at primary care and glycated hemoglobin level in patients with type 2 diabetes: a cohort study - Aurea Letícia Horbach; Julio Baldisserotto; Roger Keller Celeste (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2021)
ABSTRACT: Objective: To evaluate the association between dental visits and variation in the glycated hemoglobin index (A1C) of patients with type 2 diabetes (T2DM) with well or not well glycemic control over time. Methods: Patients with T2DM, A1C ≥ 7% (not well-controlled) and < 7% (well-controlled), who attended a primary care service and were followed up from January 2010 to May 2018. The outcome was the variation of A1C obtained from reference laboratories. At the beginning of the study, a questionnaire with behavioral, clinical, and socioeconomic information was carried out. Multiple linear regression analyses tested interaction terms of all variables with the initial glycemic level (not well-controlled or well-controlled). Results: The sample consisted of 507 people, 65% women, and 66% individuals 55 to 74 years old, followed on average for 5.4 years. There was an interaction (p = 0.01) between dental visits and initial A1C. Patients not well-controlled with at least one dental visit had an average reduction in A1C of -0.56 percentage point (95%CI -1.06 - -0.56), whereas the well-controlled group who also had at least one dental visit had an increase of 0.34 percentage point (95%CI -0.18 - 0.87). Conclusion: Dental visits were associated with an improvement in A1C of approximately a half-percentage point in patients who had the initial A1C considered as not well-controlled.